Synthesis and characterization of functionalized single walled carbon nanotubes infused cellulose acetate/poly(vinylpyrrolidone) dialysis membranes for ion separation application. Issue 4 (August 2021) - Ashraf, Muhammad Adnan; Islam, Atif; Dilshad, Muhammad Rizwan; Butt, Muhammad Arif; Jamshaid, Fahd; Ahmad, Adnan; Khan, Rafi Ullah
Abstract: In this work, a series of cellulose acetate (CA)/poly(vinylpyrrolidone) (PVP) membranes composed of different CA/PVP ratios were synthesized using 2-stage phase inversion protocol. The ions dialysis separation performance of the membranes was investigated using dialysis process with mix solution containing K +, Na +, Ni 2+ and Zn 2+ ions for separation of following pair of ions: K + /Zn 2+, K + /Ni 2+, Na + /Ni 2+ and Na + /Zn 2+ . The membrane with the highest separation factor was selected for further modification with varying amount (0.1–0.7 wt%) of acid functionalized single-walled carbon nanotubes (f-SWCNTs). The f-SWCNTs infused membranes were then characterized for their hydrophilicity, thermal stability, morphology, water uptake, contact angle, pure water flux and ion dialysis separation. The FTIR spectroscopy was also used to investigate the interactions between f-SWCNTs and membrane matrix. TGA thermograms indicated improved thermal stability of f-SWCNTs infused membranes. The morphological analysis revealed asymmetric structure and uniform distribution of f-SWCNTs in the membranes. The hydrophilicity of the modified membranes was found to be increased as confirmed by water uptake and contact angle analysis. Pure water flux was found to be decreasing with the increase in infusion of f-SWCNTs. The membranes demonstrated enhanced ions separation factor with the increase in infusion of f-SWCNTs; whereas, ions permeation flux declined. It has was found that CPC3 membrane infused with 0.5 wt% of f-SWCNTs demonstrated almost similar ions separation properties as that of CPC4 membrane (0.7 wt% f-SWCNTs) and exhibited higher water flux on the basis of which CPC3 was termed as the best performing membrane. Graphical Abstract: ga1 Highlights: f-SWCNTs infused CA/PVP blend asymmetric membranes for separation of ions. Thermal and hydrophilic properties improved with f-SWCNTs loading. Ion permeate flux decreased while separation factor increased by increasing CA content. Ion permeate flux decreased while separation factor increased by increasing f-SWCNTs. Optimum properties were achieved with 0.5 wt% f-SWCNTs loading.